Ictiofauna de un ambiente lótico suburbano : EL arroyo Rodríguez (Buenos Aires, Argentina) - Remes Lenicov, Mauricio (2005)
Fil: Remes Lenicov, Mauricio. Instituto de Limnología Raúl Ringuelet, La Plata, Argentina